The Emerging Roles of Circ-ABCB10 in Cancer - Huang, Zhenjun; Shan, Renfeng; Wen, Wu; Li, Jianfeng; Zeng, Xiaohong; Wan, Renhua (Frontiers in Cell and Developmental Biology, 2022)
Circular RNAs (circRNAs) are non-coding RNAs (ncRNAs) without 5′ caps and 3′ tails, which are formed from precursor mRNAs (pre-mRNAs) that are inversely back-spliced by exons. CircRNAs are characterized by a covalently closed circular structure and are abundantly expressed in eukaryotic cells. With the development of RNA-sequencing, it was discovered that circRNAs play important roles in the regulation of numerous human genes and are related to the occurrence, development, and prognosis of diseases. Studies in various cancers have revealed that circRNAs have both positive and negative effects on the occurrence and development of tumors. Circ-ABCB10, a circular RNA originating from exons of ABCB10 located on chromosome 1q42, has been proven to play an important role in different types of cancers. Here, we report the primary findings of recent research studies by many contributors about the roles of circ-ABCB10 in cancer and clearly formulate its influence and functions in different aspects of cancer biology, which gives us a broad picture of circ-ABCB10. Thus, this study aimed to generalize the roles of circ-ABCB10 in the diagnosis and treatment of different types of tumors and its related miRNA genes. In this way, we wish to provide a sufficient understanding and assess the future development direction of the research on circ-ABCB10.